问题
解答题
先化简,再求值: (1)(
(2)(1+
(3)
(4)
|
答案
(1)(
-x+1 x2-x
)÷x x2-2x+1
,1 x
=
•x-x+1 x(x-1)
•x,x (x-1)2
=
-x+1 x-1
,x2 (x-1)2
=
,x2-1-x2 (x-1)2
=-
,1 (x-1)2
把x=
+1代入原式=-2
=91 (
+1-1)22
;1 2
(2)(1+
)÷x-3 x+3
,2x x2-9
=
×2x x+3 (x+3)(x-3) 2x
=x-3;
把x=
+3代入原式=3
+3-3=3
;3
(3)
÷(x+2-4-x x-2
),12 x-2
=
÷4-x x-2 (x+4)(x-4) x-2
=
×4-x x-2 x-2 (x+4)(x-4)
=-
,1 x+4
把x=
-4代入原式=-3
=-1
-4+43
;3 3
(4)
÷(x-3 2x-4
-x-2),5 x-2
=
÷x-3 2(x-2) 9-x2 x-2
=
×x-3 2(x-2) x-2 (3+x)(3-x)
=-1 2((3+x)
把x=
-2代入上式得:3
原式=-
=1 2(3+
-2)3
.1- 3 4